Can poetry matter? essays on poetry and American culture - Gioia, Dana 1950- (Graywolf Press, 1992)
When Dana Gioia's essay "Can Poetry Matter?" appeared in the Atlantic in 1991, it sparked a firestorm of debate and discussion over the role of the poet in today's world - a dialogue in which Gioia participated on radio, television, and in print. One of the more stimulating and provocative figures on our literary horizon, and the author of two widely praised books of poems, Gioia is also an essayist of wide renown. This collection of essays demonstrates that Gioia's talents do not lie in the area of controversy alone. Can Poetry Matter? is an old-fashioned sort of literary book, part literary criticism, part social commentary, and part plain good reading. Addressing such subjects as the poet as businessman and New Formalism as the real avant-garde, it also includes pieces on the life and work of such diverse figures as Robinson Jeffers, Weldon Kees, Robert Bly, and Wallace Stevens. In an age when literary discourse often seems either bleached of any real content or academic to the point of inaccessibility, the essays in Can Poetry Matter? are certain to educate, provoke, and, perhaps most of all, delight readers. They also establish Dana Gioia as one of the foremost cultural observers of his generation.
Keywords: Geschichte 1930-1990; Literature and society -- United States; Poetry -- History and criticism; Lyrik; Kultur; USA; Aufsatzsammlung